Bulk and Surface Chemical Composition of Wheat Flour Particles of Different Sizes - Jiangtao Lin; Yujuan Gu; Ke Bian (Journal of Chemistry)
Chemical composition and particle size are the critical factors influencing the quality and application of flour. The present study investigated the microstructure and distribution of bulk and surface chemical composition in wheat flour particles of different size. Eight samples of wheat flour of different particle size were obtained from the same native wheat flour by sieving (sieve aperture from 25 to 112 μm). Results from scanning electron microscopy and bulk chemical composition analyze showed that flour particles of different sizes differed in microstructure, protein, and starch composition. Further analysis of protein fractions with varying solubility implied that the relative smaller flour particles (diameter <48 μm) had higher gluten protein (gliadin and glutenin) ratio (60.88–64.06%). Furthermore, amino acid analysis showed that glutamic acid was rich in the medium particles. The results of XPS showed that the surface chemical composition of wheat flour of different sizes had no correlation with the bulk chemical composition, indicating that they would have an independent effect on the quality of flour.